Studi Eksperimental Perpindahan Kalor dan Penurunan Tekanan Aliran Udara Melintasi Penukar Kalor Kompak Tabung Eliptik Susunan Berseling - , BUDI UTOMO KUKUH WIDODO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Heat exchangers of various types play very important roles in industrial processes and energy industries. Compact heat exchanger is used in applications where there is relatively small pressure in the gas fluid flowing on the outside of the tubes while the liquid fluid flowing inside the tubes. Most tubes are circular cross-section. Tube of eliptic cross-section or lenticular has obtained attention in the past few decades. There are a number of advantages possessed by eliptical and lenticular tubes. This dissertation is to examine the heat transfer characteristics of air flow across the eliptic tube bank of three columns with the 4-3-4 formation. The tubes are arranged in staggered arrangement of transverse pitch of 1.5 and 2 times the length of the minor axis and the longitudinal pitch of 1.5 times the length of the major axis. Each tube is of 0.75\" equivalent diameter and aspect ratios of 2 and 2.50. The following objective is to obtain heat exchanger performance expressed in the energy ratio, pressure drop coefficient and Nusselt number as the functions of Reynolds number, aspect ratio and the transverse pitch. Experiments are conducted in the subsonic wind tunnel with air velocity of 1 m/s to 12 m/s under uniform heat fluxes of 3.7 kW/m2, 3.8 kW/m2 and 3.9 kW/m2. The tube surface temperatures are measured at 14 nodes, while the air temperatures are measured at the entry and exit of the test section. Assuming the heat loss to the environment is very small, therefore it can be ignored, and the system operates in a steady state, then the functions are obtained as follows: